PENGARUH MODEL PEMBELAJARAN PBM TERHADAP HASIL BELAJAR IPS DI SEKOLAH DASAR - Maulana, Hendra; Asran, Mastar; Margiati, KY (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: This study aimed to test how much influence the implementation of the model problem based learning to the learning outcomes of Social Sciences at the fifth grade students of State Elementary School 36 South Pontianak. This study used an experimental method to form Pre-Experimental Design type one group pretest-posttest design. The population in this study are 22 students in which the entire population sampled. The calculation result obtained t t test 6,421 while ttabel with dk = 22-1 = 21 and a significant level (α) = 0.05 is 1.725, turns thitung ttable or ≥ 6,421 ≥ 1.697, which means a significant influence on the application model problem based learning. From the calculation of effect size (ES), of 0.90 with a relatively high criteria. This means that the model of problem based learning provide high impact on learning outcomes of Social Sciences at the fifth grade students of SDN 36 South Pontianak. Keywords: Influence, model problem based learning, Learning Outcomes